MENEJEMEN KEGIATAN EXHIBITION DI KAWASAN BANDAR SERAI PEKANBARU - Irma Febriana Siregar; Andi M. Rifiyan Arief (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Broadly speaking, the stages in performing the management include planning, organizing, implementing and supervising. Planning is the basic process of an activity and is an absolute requirement of a management activity.Management done on the art area of Bandar Serai Pekanbaru is a form of management that is done with cooperation on every existing field. Bandar Serai area is an area that has a complex function. The function used is as a function of MICE implementation location. MICE activities conducted in the form of exhibition activities are more often held. The implementation of exhibition activities in this area has a relatively high number compared to other areas in Pekanbaru that are not hotel based.Management is not only management during the activity, but how the management is done before and after the activity. In accordance with the purpose of this study, which is intended to find out how the implementation of Exhibition activities conducted by the manager of Bandar Serai area through UPT-D officials Bandar Serai reviewed based on management functions, namely: planning, organizing, directing and supervision based on theory G. Terry on P. Hasibuan's book.Keywords: Management, Management Function, Exhibition